Accessing Rights and Mitigating Revictimization: The Role of the Victim's Legal Counsel in the Swedish Criminal Justice System. (January 2022) - Carroll, Caitlin P.
Rape victims often face secondary victimization by the criminal justice system, prompting their advocates to promote a variety of procedural changes, including the provision of an independent legal counsel for victims. Sweden implemented a legal counsel for victims of sexual assault and rape in the late 1980s, yet research about their role remains limited. This article draws upon interviews with victim-lawyers in Sweden and suggests that having access to an independent legal counsel can mitigate the risks for secondary victimization by empowering victims to access their rights and providing emotional support and connectedness in the criminal justice system.